Comportamiento reproductivo del pez Opistognathus rosenblatti (Perciformes: Opistognathidae) en cautiverio - Contreras, Mauricio (2012)
Reproductive behavior of Opistognathus rosenblatti (Perciformes: Opistognathidae) in captivity. The Blue Spotted Jawfish O. rosenblatti, is an endemic species from the Gulf of California, included in the local list of protected species. With few biological reports, this species is appreciated in the aquarium industry due to its coloration and digging behaviour, and has a considerable value. With the aim to generate valuable biological information, eight fishes were caught at Loreto Natural Marine Protected Area. Captured fishes were juveniles, and just three of them were kept in an aquarium conditioned with gravel, pieces of shells and coral as substrata. Temperature and photoperiod conditions were stable, and they were supplied with a variety of live and inert feeds. Fishes reached maturity in eight months, according to literature reports, displaying mature male courtship coloration and upward movements in the water column. Fishes spawned several times over more than two years in captivity. Presences of egg masses, or some evidence of egg shell or larvae, were registered in 50 occasions. Male took care of eggs in his shelter, but never in his mouth. Egg masses had an average of 3 592 eggs, with a hatching rate close to 99%. Eggs were apparently rounded having three diameter measurements with significant differences (1.17mm mean higher diameter, SD=0.054; 1.13mm mean lower diameter, 0.058; 0.99mm mean height, 0.045; n=125). Most of corion eggs had four, rarely six filaments; with a single oil drop (0.30mm mean diameter, 0.021, n=59). Incubation lasted 10.4 days (9-14), depending on water temperature (21.0-25.3°C). Egg hatching occurred after darkness, emerging newly hatched larvae of 4.51mm mean notochord length (0.082, n=30), with reserves exhausted, eyes pigmented and mouth opened, ready to eat. This study represents the first report on this species courtship displaying, spawning and some basic characteristics of eggs masses and larvae in captivity. Also, their flexibility and adaptability of individual behaviour to particular environment conditions, lead to consider worth their commercial culture, as already occur with other species of this family.